Production of fermentable sugars from oil palm biomass via dilute acid hydrolysis - Yip, Yen Murn, 1990-, autho; Noraini Jaafar; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - UniversitiTeknologi Malaysia, 2013